Streptococcus constellatus Peritonitis and Subsequent Septic Shock following Intrauterine Device Removal - Joan Tymon-Rosario; Jessica M. Atrio; Hyun Ah Yoon; David Erlichman; Veronica Lerner (Case Reports in Obstetrics and Gynecology)
Background. Previous reports have described cases of abscess formation by Streptococcus constellatus involving the oral cavity, gastrointestinal tract, and septic thrombophlebitis of the right ovarian vein with subsequent bacteremia and septic shock. Ascending infection from the genital tract to the fallopian tubes resulting in peritonitis from Streptococcus constellatus is a rare clinical circumstance where there is minimal information in the literature to guide its diagnosis, management, and expected prognosis. Case. A 36-year-old G3P0111 developed a tubo-ovarian abscess two weeks after intrauterine device (IUD) removal and then rapidly decompensated with septic shock from peritonitis due to Streptococcus constellatus infection. The patient was also newly diagnosed with diabetes and in diabetic ketoacidosis (DKA) on presentation. She received broad-spectrum antibiotic coverage and required two exploratory surgical procedures to obtain source control. Two Interventional Radiology- (IR-) guided drainage procedures were subsequently performed to drain remaining fluid collections. Her recovery involved a prolonged ICU stay. On hospital day seventy-three, after receiving approximately 8 weeks of antibiotics and the above noted procedures the patient was discharged to a subacute rehabilitation facility. Conclusion. Streptococcus constellatus is a highly pathogenic organism once a systemic septic infection has become established that can cause an ascending genital tract infection resulting in tubo-ovarian abscess formation, peritonitis, and septic shock.